Family Empowerment Model for Type 2 DM Management: Integration of Self care Model by Orem and Family Centered Nursing by Friedman in Sikumana Health Center-Kupang - Margaretha Teli (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2019)
Background. The management of Diabetes which is very complex needs full support from the family. The family has a vital role in management type 2 diabetes at home involving diabetes diet, diabetes medication management, exercise, and also visit health care services for checking blood glucose and diabetes discussion session. Unfortunately, the family is rarely Involved in the health education session. The research aimed to identify the effect of family empowerment models: Integrated self-care model by Orem and Family-Centered Nursing by Friedman in type 2 DM management in Sikumana Health Center of Kupang. Methods. The research design was pra-experimental design with